Critical realism and the political economy of the euro - Philip Arestis; Andrew Brown; Malcolm Sawyer (Levy Economics Institute of Bard College, 2002)
This paper is concerned with two issues. First, it discusses some of the main problems and inferences the methodological approach of critical realism raises for empirical work in economics, while considering an approach adopted to try to overcome these problems. Second, it provides a concrete illustration of these arguments, with reference to our recent research project analyzing the single European currency. It is argued that critical realism provides a method that is partially appropriate to concrete levels of analysis, as illustrated by the attempt to explain the falling value of the euro. It is concluded that the critical realist method is inappropriate to the most abstract and fundamental levels of theory.
Keywords: 330